PENGARUH PERSEPSI KEBERMANFAATAN, KEMUDAHAN PENGGUNAAN, DAN RISIKO TERHADAP MINAT MENGGUNAKAN LAYANAN MOBILE BANKING DENGAN ATTITUDE TOWARD USING SEBAGAI VARIABEL INTERVENING (STUDI KASUS MAHASISWA UIN SUMATERA UTARA PENGGUNA BSI MOBILE) - Dhita Lutfiah; Fauzi Arif Lubis; Tuti Anggraini (JURNAL ILMIAH EDUNOMIKA, 2024)
With attitude towards usage as an intervening variable, this study intends to determine the link and influence of perceptions of utility, usability, and risk to interest in using mobile banking services. (Study on Mahasiswa in Sumatera Utara Using Bsi Mobile). The study employs an associative quantitative methodology to explain how perceptions of utility, usability, and risk affect interest in utilising mobile banking services, with attitude towards use serving as an intermediary variable. The study is titled "Studi Kasus Mahasiswa Uin Sumatera Utara Pengguna Bsi Mobile." Primary data came from questionnaires that respondents themselves filled out, while secondary data came from books, journals, research findings, practical work reports, and information linked to the author's research topics. The population for this study will consist of all 25.188 North Sumatra students from 2019 to 2022 (https://sumut.bps.go.id). There will be 99 participants in this study. The study's findings indicate that the Attitude Towards Using in Using Mobile Banking Services is significantly influenced by the Usability Perception variable. Keywords : Usefulness, Ease of Use, Risk, Interest, Attitude Toward using